Connecting to Young Muslims; Strengthening The Da’wah Community of Santrendelik Through Public Relations - Ayu Surita Jannah; Nadiatus Salama; Asep Dadang Abdullah (Mediakita, 2025)
The development of digital technology has led to a significant shift in da’wah practices, where young people tend to access their spiritual needs through online media. This condition poses a challenge for traditional da’wah majlis in attracting the younger generation. This research examines the public relations strategy of da’wah community in creating an attractive, responsive forum that understands the spiritual characteristics of contemporary youth. The research explores the Santrendelik da’wah community’s strategy in attracting young audiences. A descriptive qualitative method was used to comprehensively describe social reality, focusing on extracting meaning from individual experiences regarding the community’s public relations strategies. The data was collected through interviews, and analysis followed the Milles and Huberman model, which includes data reduction, presentation, and conclusion drawing. The results show a systematic mechanism of youth development through four stages: (1) research and listening, identifying the needs of the millennial generation; (2) planning and decision making, designing innovative religious social interventions; (3) communication actions, implementing the “nongkrong tobat” program; and (4) evaluation, measuring the effectiveness of the intervention.